Organic tubers for health and wealth - Suja, G.; Sreekumar, J.; Jyothi, A. N. (Indian Horticulture, 2019)
Tropical tuber crops in general and aroids like elephant-foot yam in particular respond well to organic manures. There is ample scope for production of organic tubers. Use of organically produced seed materials, seed treatment in cowdung, neem cake, bio-inoculant slurry, farmyard manure incubated with bio-inoculants, green manuring, use of neem cake, biofertilizers and ash form the strategies for organic production. Organic farming is an eco-friendly management strategy that enables 10-20% higher yield with quality tubers, maintaining soil health.